Empowering Local Communities Through Zakat to Achieve Sustainable Development Goals - Zunaidi, Arif; Maghfiroh, Fachrial Lailatul; Setiawan, Firman (IQTISHODUNA, 2024)
The Prosperous Village Livestock Program at LAZNAS Nurul Hayat Kediri City serves as a model for utilizing zakat to bolster local communities towards sustainable development goals. This qualitative case study employs document analysis, interviews, and field observations to delve into the efficacy of this program. Despite challenges in zakat fund administration and economic limitations, findings indicate its effectiveness in community empowerment through livestock company financing, training, and social network enhancement. This study uniquely focuses on zakat-driven empowerment to combat poverty and foster sustainable development at the grassroots level. By addressing the research problem of how zakat can be leveraged for long-term community development, it fills a critical gap in existing literature. Phenomenologically, the subject of this study encompasses individuals involved in or affected by the Prosperous Village Livestock Program, while the object is the empowerment process facilitated by zakat utilization.